Workplace Violence and Long-term Sickness Absence: Assessment of the Potential Buffering Effect of Social Support in Two Occupational Cohort Studies. Issue 10 (October 2020) - Hoffmann, Sofie Have; Bjorner, Jakob Bue; Xu, Tianwei; Mortensen, Jesper; Török, Eszter; Westerlund, Hugo; Persson, Viktor; Aust, Birgit; Rod, Naja Hulvej; Clark, Alice Jessie
Abstract : Objectives: We aimed to determine the effect of workplace violence on long-term sickness absence, and whether social support from supervisors and colleagues buffer this effect. Methods: Information on workplace violence and social support were derived from the Danish Work Environment Cohort Study in 2000, 2005, and 2010 and the Swedish Longitudinal Occupational Survey of Health in 2006 and 2008. Individual- and joint-effects on register-based long-term sickness absence were determined using logistic regression models for repeated measurements. Cohort-specific estimates were combined in random effect meta-analyses. Results: Workplace violence and low social support were independently associated with a higher risk of long-term sickness absence, and we did not find evidence of an interaction. Conclusion: Exposure to workplace violence is a risk factor for long-term sickness absence while social support is associated with a lower risk of long-term sickness absence. Abstract : Supplemental Digital Content is available in the text